2020
DOI: 10.1142/s1793524520500254
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of cholera in a periodic environment with control actions

Abstract: In this paper, we studied the impact of sensitization and sanitation as possible control actions to curtail the spread of cholera epidemic within a human community. Firstly, we combined a model of Vibrio Cholerae with a generic SIRS cholera model. Classical control strategies in terms of the sensitization of population and sanitation are integrated through the impulsive differential equations. Then we presented the theoretical analysis of the model. More precisely, we computed the disease free equilibrium. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Under stress, this pathogen assumes a viable but not culturable state, becoming undetectable to traditional bacteriological techniques (Codeco, 2001;Colwell, 1996). Classical control strategies in terms of the sensitization of population and sanitation are integrated through the impulsive differential equations (Kolaye et al, 2020). More recently, (Martins et al, 2022) in their study of mathematical model for prevention and control of cholera transmission in a variable population developed an extended SIRB deterministic epidemiological model for cholera and strictly analyzed it to ascertain the impact of immigration in cholera transmission and to assess the suitability of the various control measures (also see Olaniyi and Ogbonna, 2021).…”
Section: Suggested Citationmentioning
confidence: 99%
“…Under stress, this pathogen assumes a viable but not culturable state, becoming undetectable to traditional bacteriological techniques (Codeco, 2001;Colwell, 1996). Classical control strategies in terms of the sensitization of population and sanitation are integrated through the impulsive differential equations (Kolaye et al, 2020). More recently, (Martins et al, 2022) in their study of mathematical model for prevention and control of cholera transmission in a variable population developed an extended SIRB deterministic epidemiological model for cholera and strictly analyzed it to ascertain the impact of immigration in cholera transmission and to assess the suitability of the various control measures (also see Olaniyi and Ogbonna, 2021).…”
Section: Suggested Citationmentioning
confidence: 99%
“…We also proposed a mathematical model of cholera in a periodic environment with public health worker interventions such as sanitation or campaign awareness. In this study, we combined the bacteria model that we developed and studied in [7] with a S-I-R-S human cholera model in [8]. The findings showed that the control cholera should consider both sensitization and sanitation with a strong focus on sanitation.…”
Section: Related Workmentioning
confidence: 99%